ENHANCING STUDENTS’ SPEAKING PERFORMANCE THROUGH A DAY IN MY LIFE CONTENT’ ON - Huka, Britshy Rosanadya; Basikin, Basikin; Ximenes, Adalciza Agusta; Manafe, Thedy Hardi; Relmasira, Mega Victoria; Kawai, Santi; Kesaulija, Anggelvania Liany (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
This study investigates the effectiveness of using "A Day in My Life" content on TikTok to improve the speaking performance of eleventh-grade tourism department students at SMK Bahari Ambon. Despite the growing popularity of ICT tools in education, many students still struggle with speaking skills, particularly in contexts that require confidence and fluency. This research aimed to determine how TikTok, as an innovative educational tool, could impact students' speaking abilities. The study involved 27 students and was conducted over three cycles, utilising a mixed-method approach that included project presentations as tour guides, video projects at tourist attractions in Ambon, observation checklists, interviews, and scripts of tourist attractions. The findings revealed a significant improvement in students' speaking skills, with average scores increasing from 48 in the first cycle to 71.5 in the second cycle and reaching 97.7 in the third cycle. Descriptive data showed that using TikTok enhanced students' confidence, reduced their fear of making mistakes, and encouraged continuous practice. Both quantitative and qualitative results highlighted the importance of consistent speaking practice, appropriate media use, and engaging classroom activities in improving speaking performance. The study concludes with implications for educators and suggests that integrating "A Day in My Life" content on TikTok is an effective strategy for enhancing students' speaking performance in the tourism department.